Pemanfaatan Biopori Sebagai Solusi Lingkungan Pencegahan Banjir dan Pengelolaan Sampah Organik - Dharmayanti, Amilita M.R.; Parmita, Ade Wahyu Y.P.; Tajalla, Gusti U.N.; Masdar, Muhammad Rafli; Danuarta, Rayhan Kurnia; Pongsapan, Navalma Glory Sankara; Sumomba, Arya Pandu Dewanata (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
Flooding is a situation where an area is inundated by large amounts of water. Floods occur due to high precipitation levels that are not accompanied by an adequate drainage system and there are still large piles of rubbish dumped carelessly around the village. For this reason, we from the 2Q-a community services ITK group are trying to hold outreach and practice for making biopore infiltration holes in the RT 07 area, Sungai Merdeka Village, KM.36, Samboja, East Kalimantan. The results that can be obtained from the biopore infiltration hole socialization activities such as: (1) Community insight and knowledge increases regarding the creation of biopore infiltration hole, (2) The community has awareness of how organic waste should be put into these biopore infiltration hole, (3) The community can manage compost fertilizer from the results of the biopore infiltration hole. It is hoped that this program will be sustainable and provide many benefits so that the community can overcome the problem of organic waste which is still managed by burning.